The Stigma of Having an Abortion: Development of a Scale and Characteristics of Women Experiencing Abortion Stigma. Issue 2 (2nd May 2013) - Cockrill, Kate; Upadhyay, Ushma D.; Turan, Janet; Greene Foster, Diana
<x xml:space="preserve">Abstract</x> Context Although abortion is common in the United States, women who have abortions report significant social stigma. Currently, there is no standard measure for individual‐level abortion stigma, and little is known about the social and demographic characteristics associated with it. Methods To create a measure of abortion stigma, an initial item pool was generated using abortion story content analysis and refined using cognitive interviews. In 2011, the final item pool was used to assess individual‐level abortion stigma among 627 women at 13 U.S. Planned Parenthood health centers who reported a previous abortion. Factor analysis was conducted on the survey responses to reduce the number of items and to establish scale validity and reliability. Differences in level of reported abortion stigma were examined with multivariable linear regression. Results Factor analysis revealed a four‐factor model for individual‐level abortion stigma: worries about judgment, isolation, self‐judgment and community condemnation (Cronbach's alphas, 0.8–0.9). Catholic and Protestant women experienced higher levels of stigma than nonreligious women (coefficients, 0.23 and 0.18, respectively). On the subscales, women with the strongest religious beliefs had higher levels of self‐judgment and greater perception of community condemnation than only somewhat religious women. Additional differences were found by race, age, education, religiosity and motherhood status on the subscales. Conclusion This valid and reliable scale can be used in research examining abortion stigma and related outcomes (e.g., women's health, relationships and behavior). The scale can also be used to evaluate programs and interventions that aim to reduce the stigma experienced by women who have abortions.